AKULTURASI NILAI LOKAL : ANALISIS TATA KELOLA ALAS GUMITIR DALAM PEMBANGUNAN PEREKONOMIAN MASYARAKAT DESA - Tri Cahyono; Dwi Budi Santoso; Iswan Noor (Jurnal Ekonomi Pembangunan, 2017)
The main objectives of this research are: (i) To analyze the factors that influence the motivation of community participation in managing Alas Gumitir in terms of acculturation of local value, and (ii) To know how the role of acculturation of local value in improving the quality of community participation Managing Alas Gumitir. The method used in this research is descriptive quantitative by taking samples in Kalibaru Manis Village, Kalibaru Subdistrict, Banyuwangi Regency. While the data analysis tools used are factors and discriminant. Factor analysis is used to determine the motivation of the community supported by the application of acculturation to local values. While discriminant is used to know the role of acculturation of local value in improving the quality of participation. The result of factor analysis shows that most motivated communities participate in managing Alas Gumitir as a coffee plantation due to: (i) increased production, (ii) income increase, (iii) land area, (iv) low production cost, (V) labor availability . Surely this is supported by the values of local wisdom which increasingly streamline and streamline governance in the Alum gumitir coffee plant. While discriminant analysis is obtained: (i) the community assumes that the existence of informal sanctions, the effectiveness of sanctions implementation, and institutions or parties imposing sanctions can improve the quality of management participation of Alas Gumitir, (ii) Informal sanctions by the majority of low-income people are considered unable to improve the quality Management participation of Alas Gumitir.